2007
DOI: 10.1152/ajplung.00458.2006
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus induces insensitivity to β-adrenergic agonists in mouse lung epithelium in vivo

Abstract: Davis IC, Xu A, Gao Z, Hickman-Davis JM, Factor P, Sullender WM, Matalon S. Respiratory syncytial virus induces insensitivity to ␤-adrenergic agonists in mouse lung epithelium in vivo. Am J Physiol Lung Cell Mol Physiol 293: L281-L289, 2007. First published April 13, 2007; doi:10.1152/ajplung.00458.2006 is the most common cause of bronchiolitis in infants and children worldwide. We wished to determine whether intratracheal administration of ␤-agonists improved alveolar fluid clearance (AFC) across the distal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 51 publications
(46 reference statements)
9
52
1
Order By: Relevance
“…One difference between the studies of Planes and colleagues (1) and ours is the baseline values of AFC in C57BL/6 mice. Planes and colleagues reported values of 17% of instilled volume per 30 minutes, whereas our AFC values (consistent with our previous work [20,37,48]) are closer to 30% of instilled volume per 30 minutes. In our experiments, A1AT decreased AFC to 12%, which is similar to the baseline value of Planes and colleagues (1).…”
Section: Discussionsupporting
confidence: 92%
“…One difference between the studies of Planes and colleagues (1) and ours is the baseline values of AFC in C57BL/6 mice. Planes and colleagues reported values of 17% of instilled volume per 30 minutes, whereas our AFC values (consistent with our previous work [20,37,48]) are closer to 30% of instilled volume per 30 minutes. In our experiments, A1AT decreased AFC to 12%, which is similar to the baseline value of Planes and colleagues (1).…”
Section: Discussionsupporting
confidence: 92%
“…A standard curve was prepared by assaying known concentrations of bovine serum albumin in 0.9% NaCl. AFC values were calculated as described before (24,32). In some cases mice were anesthetized with isoflurane 15 min post-Cl 2 exposure, and 100 l of saline containing either trypsin (5 M) or vehicle were instilled dropwise in their nostrils.…”
Section: Methodsmentioning
confidence: 99%
“…However, the effects of Cl 2 inhalation on Na ϩ -dependent alveolar fluid clearance (AFC) in vivo as well as the mechanisms by which Cl 2 and HOCl damage ENaC have not been investigated. This is an important area of research as damage to ENaC has been associated with abnormal fluid transport in various forms of lung injury (7,(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…While initial studies of adrenalectomized animals (8,45) or desensitization of b-receptors (81, 82) note no net effect on lung water content or basal alveolar fluid clearance, a more recent study showed reduced basal alveolar fluid clearance in adrenelectomized mice (83). The differences between these studies may be due to inability to (9) similarly reveal normal water content when uninjured but decreased ability to clear excess water from the airspace and more pulmonary edema and decreased survival from acute lung injury (hyperoxia).…”
Section: Maintenance Of Alveolar Fluid Homeostasismentioning
confidence: 99%